2012
DOI: 10.1111/j.1475-682x.2012.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Pro‐Environmental Intentions: A Cross‐National Perspective on the Influence of Self‐Enhancement Values and Views on Technology*

Abstract: While many studies have addressed the complex relationship between gender and environmental constructs, few have attempted to determine just how gender influences environmentalism. We argue that the interaction of gender with other sociocultural variables must be examined. Our study includes two of these variables: technological values and self‐enhancement values. Study results indicate that the effect of gender on environmental intentions is moderated by these two variables. This is established in a multicoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 69 publications
2
18
0
3
Order By: Relevance
“…While these theories suggest higher eco-attitude levels for women compared to men, a few research studies have found the opposite results and showed that men have a higher positive eco-attitude and concern compared to women [60,61]. Men can also be highly involved with pro-environmental behavior and have a high level of environmental attitude and concern.…”
Section: Gender Differencementioning
confidence: 99%
“…While these theories suggest higher eco-attitude levels for women compared to men, a few research studies have found the opposite results and showed that men have a higher positive eco-attitude and concern compared to women [60,61]. Men can also be highly involved with pro-environmental behavior and have a high level of environmental attitude and concern.…”
Section: Gender Differencementioning
confidence: 99%
“…Some scholars claim that value orientation accounts for the gender differences in environmental concern (Stern et al, 2005). Other sociobiological theories explain that the reproductive-roles of females set the context for caring for others, and position females in closer with concerns about environmental deprivation (Pettus, 1997;Mobley & Kilbourne, 2013). Even though there are many studies investigating the influence of gender on green behavior, a consensus has not been reached (Akehurst, Afonso, & Gonçalves, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, female college students ranked the environmental certification of a wooden CD rack as a more important attribute compared to other attributes, such as wood type, price and storage size, when compared to males (Anderson & Hansen, 2004). On the other hand, recent studies claimed it is still unclear whether females or males are more environmental motivated (Mobley & Kilbourne, 2013;Xiao & Hong, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations